Nor Afifah, daughter of UMP professor, receives Vice-Chancellor Award - Nurul Ateeqah, Othman; Nur Hartini, Mohd Hatta (2022)
PAYA BESAR, August 6, 2022 - The daughter of Universiti Malaysia Pahang (UMP) lecturer, Professor Dr. Abdullah Ibrahim, Nor Afifah Abdullah, 24, received the Vice-Chancellor Award at the UMP 16th Convocation Ceremony which took place at the UMP Sports Complex, Gambang Campus.